The Difference between Coagulation Profile and Fibrinolysis in Acute and Chronic Leukemia Patients - Limijadi, Edward Kurnia Setiawan; Devi, Wivina Riza; Tjitradinata, Cynthia (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2025)
The incidence of acute and chronic leukemia has been increasing for years resulting in many complications, one of them being hypercoagulability. Evaluation can be conducted using coagulation testing, including PT, aPTT, and fibrinogen levels, as well as fibrinolysis assays, such as D-dimer levels. Studies about these parameters between acute and chronic leukemia in the first diagnosis of leukemia need to be evaluated. This study aimed to evaluate the difference in coagulation and fibrinolysis profiles between acute and chronic leukemia. This study was a cross-sectional observational analysis of 34 acute and chronic leukemia patients in Ulin Government Hospital, Banjarmasin from October 2019 to February 2020. PT, aPTT, fibrinogen level, and D-dimer were analyzed on COA Lab 1000. Independent T-test and Mann-Whitney test were used to analyze data. The test results of PT, aPTT, fibrinogen, and D-dimer levels, for acute and chronic leukemia, were 13.96±1.86 vs. 16.73±4.74 seconds (p=0.029); 39.63±2.43 vs. 45.87±13.98 seconds (p=0.154); 286,18±180,58 vs. 328,81±150,63 mg/dL (p=0.459); and 746±3.392 vs. 1,466.56±445,86 µg/L (p=0.731), respectively. Significant differences were found in Prothrombin Time (PT) between acute and chronic leukemia patients, while no notable distinctions were observed in activated Partial Thromboplastin Time (aPTT), fibrinogen levels, or D-dimer levels.